Generation of Subpicosecond Pulse Trains in Fiber Cascades Comprising a Cylindrical Waveguide with Propagating Refractive Index Wave - Aleksei Abramov (MDPI AG, 2021)
A cylindrical waveguide structure with the running refractive index wave has been recently demonstrated as a means for the generation of high-repetition-rate pulse trains. The operation mechanism involves a proper combination of the frequency modulation and modulation instability simultaneously experienced by the input continuous wave (CW) signal as it propagates through the cylinder waveguide. Here, we explore the same idea but employ the cylindrical waveguide only as a part of the cascaded optical fiber configuration now comprising both passive and active optical fiber segments. The new system design enables the improved control of the pulse train formation process in the cascaded system elements, relaxes strong requirements for the CW signal power, and provides an additional optical gain for the advanced pulse peak power scaling. In particular, using a low-amplitude, weakly modulated, continuous wave as an input signal we explore and optimize the nonlinear mechanisms underlying its cascaded transformation into the train of kilowatt peak power picosecond pulses.